The temporal expression pattern of alpha-synuclein modulates olfactory neurogenesis in transgenic mice - Schreglmann, Sebastian R.; Regensburger, Martin; Rockenstein, Edward; Masliah, Eliezer; Xiang, Wei; Winkler, Jürgen; Winner, Beate (PLoS ONE, 2015)
Adult neurogenesis mirrors the brain´s endogenous capacity to generate new neurons throughout life. In the subventricular zone/ olfactory bulb system adult neurogenesis is linked to physiological olfactory function and has been shown to be impaired in murine models of neuronal alpha-Synuclein overexpression. We analyzed the degree and temporo-spatial dynamics of adult olfactory bulb neurogenesis in transgenic mice expressing human wild-type alpha-Synuclein (WTS) under the murine Thy1 (mThy1) promoter, a model known to have a particularly high tg expression associated with impaired olfaction.Survival of newly generated neurons (NeuN-positive) in the olfactory bulb was unchanged in mThy1 transgenic animals. Due to decreased dopaminergic differentiation a reduction in new dopaminergic neurons within the olfactory bulb glomerular layer was present. This is in contrast to our previously published data on transgenic animals that express WTS under the control of the human platelet-derived growth factor ? (PDGF) promoter, that display a widespread decrease in survival of newly generated neurons in regions of adult neurogenesis, resulting in a much more pronounced neurogenesis deficit. Temporal and quantitative expression analysis using immunofluorescence co-localization analysis and Western blots revealed that in comparison to PDGF transgenic animals, in mThy1 transgenic animals WTS is expressed from later stages of neuronal maturation only but at significantly higher levels both in the olfactory bulb and cortex.The dissociation between higher absolute expression levels of alpha-Synuclein but less severe impact on adult olfactory neurogenesis in mThy1 transgenic mice highlights the importance of temporal expression characteristics of alpha-Synuclein on the maturation of newborn neurons.
EVALuna2:4712